Can the Philippine auto industry survive smuggling? - Aldaba, Rafaelita M. (2013)
This Policy Notes analyzes the exacerbating issue of auto smuggling in the country. It shows the murky policy environment that has hampered efforts to address it and examines the extent of its negative impacts on government revenues and in our bid to develop a globally competitive auto industry.
Keywords: Smuggling; Automobile industry